2007
DOI: 10.1038/sj.ejcn.1602807
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations and trends in weight and arm circumference of non-pregnant rural Senegalese women, 1990–1997

Abstract: Objective: To describe levels, monthly variations and trends in weight and arm circumference of non-pregnant lactating women living in the Sahel, characterized by one short yearly rainy season (July-October). Methods: A mixed unbalanced cross-sectional longitudinal observational study conducted at 3, 5, 7 and 10 months postpartum among 3869 women living in the Sine area in central Senegal who had brought their infants into dispensaries for immunization from January 1990 to February 1997, and 1-5 consecutive ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…No seasonal variation in BMI in pregnancy was found in the present study, whereas studies performed in nonpregnant women have reported an increase in BMI in winter months [9,10]. Different food habits, less exercise, high calorie intake, and less energy expenditure during winter have been proposed as factors influencing the increase in BMI [11].…”
Section: Discussionmentioning
confidence: 77%
“…No seasonal variation in BMI in pregnancy was found in the present study, whereas studies performed in nonpregnant women have reported an increase in BMI in winter months [9,10]. Different food habits, less exercise, high calorie intake, and less energy expenditure during winter have been proposed as factors influencing the increase in BMI [11].…”
Section: Discussionmentioning
confidence: 77%
“…Several studies of subsistence agriculturalists also point to a negative energy balance during seasons when the activity of the community is at its highest. The average body mass of 3,869 Senegalese women declined by 2.5-3.9 kg during the summer months; vigorous agricultural work was presumed to have caused a negative energy balance, although at the same time arm circumferences had increased by an average of 1 mm/month (Simondon et al 2008). Similarly, the body mass of Thai rice farmers showed a seasonal decrease of 1.3 kg in males and 2.5 kg in females, apparently with little associated change in energy intake, suggesting that food intake had not increased to meet seasonal increases in energy expenditure (Murayama 2005).…”
Section: Under-developed Societiesmentioning
confidence: 98%
“…37 Women of a nonpregnant rural African female population, the Senegalese women, tended to have higher weight in dry season (March and April), followed by lower weight in rainy season (September-November) at the end of each year, when agricultural labor consumed the stored energy. 38 A longitudinal study involving 202 Chinese infants in Chengdu City and 174 Hong Kong infants in their first 2 years of life showed that the weight gained faster in winter and slower in summer. 39 Thus, statistical analysis using only one cross-sectional BMI measurement is likely to yield biased conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…As season changes affect weight gain, [37][38][39] we took cautions in choosing an appropriate parameter to reflect the situation. In addition, possible statistical biases were avoided by including covariates in the analysis.…”
Section: Methodsmentioning
confidence: 99%